Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68029
|View full text |Cite
|
Sign up to set email alerts
|

Speed Line Computation of a Transonic Compressor Stage With Unsteady CFD Methods

Abstract: The flow through a transonic compressor stage is dominated by unsteady effects such as shock propagation and wake shedding. An accurate prediction of the performance of a compressor, i.e. operating range and efficiency, may require the modeling of unsteady effects. Steady CFD methods cease to converge too early when the stall limit is approached. Efficient unsteady CFD methods such as the transient time-inclining (TI) method and the perturbation based non-linear harmonic (NLH) method perform better and are bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is a second order cell-centered finite volume solver for structured multiblock meshes. The code was already successfully employed in different circumstances to represent unsteady flow patterns of tip loaded transonic axial and radial compressors operating at near stall conditions [18][19][20].…”
Section: The Flow Solvermentioning
confidence: 99%
“…This is a second order cell-centered finite volume solver for structured multiblock meshes. The code was already successfully employed in different circumstances to represent unsteady flow patterns of tip loaded transonic axial and radial compressors operating at near stall conditions [18][19][20].…”
Section: The Flow Solvermentioning
confidence: 99%
“…Some of these present results from multistage calculations but only at design speed [2][3][4][5] while others present results at offdesign speeds but only for a single stage [6]. Others compare steady and unsteady results but only for a single stage and at design speed [7][8][9]. Further single stage unsteady simulations have been presented for part speed calculations [10][11][12] and at design speed [13][14][15][16][17], including Large Eddy Simulations (LES) [18], however, none of these compare the unsteady simulations to steady simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature the TT method has shown very promising results in terms of predicting turbo machinery performance data as Biesinger et al (2010) demonstrated by the example of a one stage case (inlet guide vane (IGV) and rotor) of the 1.5 stage transonic Purdue compressor and later on the full 1.5-stage case (Biesinger et al (2012)). Cornelius et al (2013Cornelius et al ( , 2014 investigated the multistage extension of the TT method on a modified 2.5-stage version of the 4-stage axial Hannover Compressor and a Siemens 6-stage axial compressor rig ("PCO Rig").…”
Section: Introductionmentioning
confidence: 99%